Mid-Cavitary Obstruction in Hypertrophic Cardiomyopathy (HCM): A Rare Case Report and Management Approach - Bharadwaj, Rajeev; Boruah, Deb; Barman, Bhupen; Kalita, Suman (Acta medica Lituanica, 2025)
Hypertrophic cardiomyopathy (HCM) with mid-cavitary obstruction (MCO) is an uncommon condition affecting approximately 10% of HCM patients which is associated with serious outcomes, including sudden cardiac death and heart failure. We present the case of a 43-year-old male with type 2 diabetes mellitus who experienced worsening dyspnea and palpitations, leading to the diagnosis of HCM with MCO without outlet obstruction. Cardiac MRI with gadolinium contrast reveals significant mid-cavitary obstruction without left ventricular outflow tract obstruction with a scar burden of 27% and the absence of other high-risk factors such as apical aneurysm and NSVT runs on Holter monitoring. The patient was treated conservatively with the oral beta-blocker therapy, resulting in symptomatic improvement. Given the high risk of an adverse outcome, it is crucial to recognise MCO early and provide the appropriate treatment. This case report discusses the presentation, diagnosis, and management of a patient with HCM and mid-cavitary obstruction, highlighting the unique treatment considerations associated with this condition.Take home message1. Mid-cavitary obstruction (MCO) in hypertrophic cardiomyopathy (HCM) is associated with high-risk outcomes of sudden cardiac death and heart failure.2. While beta-blockers can improve symptoms in many MCO patients, treatment should be personalized based on the symptom severity and risk factors.3. Patients with MCO are at risk of complications like apical aneurysms, thromboembolism, and arrhythmias.
Keywords: hypertrophic cardiomyopathy; left ventricle outflow tract obstruction; mid-cavitary obstruction; heart failure; beta-blocker therapy; conservative management; risk stratification